Dust in the Universe:similarities and differences - Krishna Swamy K S (World Scientific, 2005)
The study of dust in the universe is an exciting area in current astronomy. Dust formed during an earlier epoch could be different from that formed at a later time, but the nature and composition of dust is not presently understood in its entirety. The comprehensive study presented in this book provides a much needed critical analysis of different types of dust in the universe. The information derived from presolar grains from comets, meteorites and interplanetary dust particles as well as the relevant laboratory studies are discussed. This should help in our goal of understanding the evolution of dust with cosmic time.
Keywords: Cosmic dust; Interstellar matter